(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2001)
In this tentative to define behaviorism as a scientific project, priority is given to descriptions of its fundamental values, its vision of man and the universe, its definition of knowledge, its semantic strategies and its attitude in relation to the notion of scientific truth. The assumptions of the approach are sketched in a way that makes possible the comparison with other scientific methods within psychology. Its history is traced in terms of paradigmatic continuity and discontinuity. Without sticking to didactically convenient dichotomies like the opposition between the radical and methodological varieties, we explore the movement’s inherent contradictions and their potential implications for its identity as an approach and for its future directions.